Women and gender equity in academia through the conceptual lens of care. Issue 1 (2nd January 2022) - Gaudet, Stéphanie; Marchand, Isabelle; Bujaki, Merridee; Bourgeault, Ivy Lynn
ABSTRACT: Even though academics are routinely engaged in care activities for their students, colleagues, institutions, and families, care is often overlooked in the culture of academia. This study focuses on how care work affects gender equity in academia, along with work and personal lives of women academics. Through female professors, the study explores the extent, variety, and lived experiences of care practices in academia. Utilizing care and gender theories in an organizational context, we analyzed qualitative interviews with twenty-two female academics from two Canadian universities, purposively selected to represent different disciplines and stages in the academic career trajectory. Regarding their life and health trajectories, our interviewees spontaneously utilized a vocabulary of care to describe their teaching, supervision, and administrative tasks. This acknowledgment of care as an important aspect of academic practice can be helpful in addressing gender inequalities in academia. Specifically, self-care remains a largely overlooked—yet important—category of care theory. Based on our fieldwork, we argue that self-care needs to be more closely and extensively studied to create a more supportive academic work culture.